Weaving as Touristic Drive in Pringgasela; Motive and Philosophy - Zaitun Zaitun; Hasan Basri; Muhammad Adi Junaidi; Muhammad Ramli; Irwan Rahadi; Muh Hilmi Pauzi (Enrichment : Journal of Management, 2022)
Pringgasela inhabitants have been practising Weaving for ages. Most locals who participated are women dwellers in support of economic empowerment. This research intentionally investigates; 1) the profound history of weaving in Pringgasela, 2) equipment used for Weaving and dye materials, and 3) motifs and philosophy of Weaving. We, furthermore, deploy the qualitative as a research approach elaborating three main focuses of the study—direct observation and interviews are conducted to collect data from resources and documentation. Participants being selected are mostly citizens, business actors, government agencies in charge of developing tourism. The results show that most woven fabrics are traditional dyeing models and prefer synthetic dyes because they are more in demand by young people. Although the process of making today has been developed, natural material is still maintained for local preservation purposes. In support of local economic empowerment, Pringgasela inhabitants have practised weaving for ages. Various motifs are continuously introduced in which local wisdom is still a prominent attractive feature for buyers and visitors. Barriers to marketing in this article are presented.